Pengaruh Model Total Physical Respon Terhadap Kemampuan Menulis Deskriptif Siswa Kelas X Peksos SMKN 9 Medan - Aulia Meylani; Syafina Maulani; Lulu Ilmanun; Fitra Audina (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This research discusses the influence of the total physical response model on students' descriptive writing abilities. This research refers to the total physical response model which influences students' descriptive writing abilities. Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential. A model is said to be good and suitable if it can lead to the intended goal. The Total Physical Response (TPR) model in studying descriptive writing skills is a better model because it makes students feel happy, free from stress, everything taught can be remembered for a long time, they don't have to think hard to understand and store something, it combines physical movements with intellectual activity and the use of all the senses can have a big impact on learning. The data collection technique was carried out using quantitative descriptive research which objectively describes the results obtained by students in the descriptive writing ability test using the total physical response model. The total physical response model is a learning model that begins with commands or utterances accompanied by movements from the teacher which are then followed by students according to the (motor) movements they have seen from the teacher.